Case Report: Chemotherapy and Radiotherapy Combined With DC-CIK for Pulmonary and Mediastinal Metastases From Nasopharyngeal Carcinoma - Gan, Yi-Xiu; Li, Gui-Hua; Ou, Xue; Wang, Chun-Hui; Du, Qing-Hua (Frontiers in Oncology, 2022)
Introduction The optimal treatment for pulmonary and mediastinal metastasis of nasopharyngeal carcinoma (NPC) is still controversial, and the therapeutic effect is poor recently. In one case, we demonstrated a long-term survival after postoperative chemoradiotherapy combined with dendritic cell and cytokine-induced killer (DC-CIK) immunotherapy for pulmonary and mediastinal metastases from NPC. Baseline Characteristics A 53-year-old woman was admitted to our hospital in June 2008. Pathological biopsy revealed a poorly differentiated squamous cell carcinoma located in the nasopharynx with the invasion of internal pterygoid muscles, the sphenoid bone, and unilateral neck lymph node metastasis. No distant metastases were observed. The stage of NPC was T3N1M0 III (AJCC8). The patient received concurrent chemoradiotherapy for primary lesion and neck lymph nodes and achieved complete remission (CR) of the disease after 3 months. Follow-up at 3-month intervals was carried out. Pulmonary and mediastinal lymph node metastases were found in July 2009. The patient then underwent right upper lobectomy and mediastinal lymph node dissection and five cycles of gemcitabine and cisplatin (GP) regimen chemotherapy, following radiotherapy and DC-CIK immunotherapy. Results After a follow-up time of 13 years, no tumor recurrence or metastasis and severe adverse reactions were found. Conclusion Postoperative chemotherapy and radiotherapy in combination with DC-CIK immunotherapy may produce a synergistic therapeutic effect on patients with mediastinal lymph node metastasis from NPC.